Meningkatkan Kinerja Unit Komposter Dalam Memproduksi Kompos Organik Cair - Nurjazuli nurjazuli; Hanif Tegar Muktiana Sari (Dampak, 2019)
Background: Domestic waste is a side product of human activities in the fullfill of daily needs. Organic waste is the most number of waste produced by the household with 60-70% of quantity. And It increases time to time and becomes a big burden for the goverment to manage. Community participation is very expected in handling It’s organic waste. It is needed an appropriate technology wich is implemented by community easily. The author had ever done action research using a technology in producing organic liquid compost from domestic waste, but It had low performance in producing both liquid compost and slow process. Based on this research result, It is very important to create new inovation to increase the performance of composter unit. So, this research aimed to increase the performance of composter unit in producing organic liquid compost from domestic waste.Method: It was an experimental research using pra-experimental design. One unit of composter which was modified on outlet size was used during the research running. To increase the speed in producing liquid compost, It was modified by increasing consentration and volume of Effective Microorganism 4 (EM4) solusion twice in dosering as stater the process. Observation of the process was done to gain information qualitatively on performance canges of composter unit. The data would be analyzed descriptively to illustrate the process canging  and product over the research running.Result: The resarch result showed that modification on outlet size can increase the operational performance of composter unit. The 0,5 inchi of outlet size can  increase the performance of composter unit in releasing liquid compost. So, It can improve the outlet performance compared to previous research. Consentration 10% and 20 times spray of EM4 solution can increase the speed and voluve of liquid compost produced by composter unit. The production of liquid compost increase rapidly on the second month after the process running. The liquid compost production is harvested every three days periodically. The liquid compost produced is one liter per day in average. Conclusion: This research concluded that modification on both outlet size and consentration  and volume of EM4 as starter can increase the performance of composter unit in producing organic liquid compost.